Behavior, Conditions and Impact of Persons Able and Unable to Quit Smoking in Patong Village, Hat Yai District, Songkhla Province - Chaikuntaveechot, Pirasinee; Janyaem, Kanda; Jorajit, Sujitra (Journal of Health Science of Thailand, 2018)
This qualitative research was aimed at investigating smoking behavior, which related to persons able and unable to quit smoking their conditions and impacts. The target informants were 30 males aged 12 years or over. Among all, 15 of them were able to give up smoking, while 15 of them were unable to give up smoking. Data were collected through in-depth interviews, and analyzed by employing frequency distribution and content analysis. It was found that in terms of smoking behavior, the majority of them started to smoke at the ages of 16 – 20 years. The most common reason for starting to smoke was curiosity and being adventurous in life. The most common reason for continuing to smoke was being persuaded by friends and cigarettes were provided for. Apart from that, the types of environment was a factor as well such as peers, stress or problems, the number of smoking family members and tempting advertisement with smoking shown effectively. With regard to their smoking habits, most of them finished the whole cigarette, were chain smoking, smoked approximately 11 – 20 cigarettes daily, and smoked filtered cigarettes and tobacco. The conditions related to the ability to give up smoking successfully, were mainly health problems, negative thoughts towards smoking, feeling worried about their family members, being motivated by requests from acquaintances and being self-disciplined. Also, the conditions related to the inability to give up smoking were being addicted to smoking, stress, socializing and being with friends, and not knowing how to quit smoking. The impacts of persons able to give up smoking were improved health, better sleep, and more appetite, in good mood, not emotional and not bringing adverse effects to oneself and any other while wasting no money and their improved relationships with others. On the other hand, the impacts of being unable to give up smoking were to compromise their own health and others’ on their own expense. Moreover, once deprived of cigarette, they often turned moody. Smokers could experience being rejected and looked down upon as a poor role model.